Challenges and Opportunities in Shaping a Generation with Noble Character by Instilling Values of Tolerance - Lucky Antonio; Tri Subekti (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This article investigates the ways in which religious education can integrate values of tolerance and moderation in an attempt to develop students into moderate and tolerant members of society. This study uses a comprehensive research process to investigate teaching strategies such as value-based learning, contextual, collaborative, dialogue, and simulation techniques. Based on the results of the analysis, applying these principles discourages extremism while fostering tolerance and respect for one another's differences. By encouraging values of diversity and balance, Islamic religious education contributes to the development of moral character and social harmony.